Differential Expression of Resistant and Efflux Pump Genes in MDR-TB Isolates - AlMatar, Manaf; Var, Işıl; Kayar, Begüm; Köksal, Fatih (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Numerous investigations demonstrate efflux as a worldwide bacterial mode of action which contributes to the resistance of drugs. The activity of antibiotics, which subjects to efflux, can be improved by the combined usage of efflux inhibitors. However, the efflux role to the overall levels of antibiotic resistance of clinical M. tuberculosis isolates is inadequately comprehended and is still disregarded by many. Methods: Here, we assessed the contribution of resistant genes associated with isoniazid (INH) and rifampin (R) resistance to the levels of drug resistance in the (27) clinical isolates of MDR-TB. Additionally, the role of the resistance for six putative drug efflux pump genes to the antibiotics was investigated. The level of katG expression was down-regulated in 24/27 (88.88%) of MDR-TB isolates. Of the 27 MDR-TB isolates, inhA, oxyR-ahpC, and rpoB showed either overexpression or up-regulation in 8 (29.62%), 4 (14.81 %), and 24 (88.88%), respectively. Moreover, the efflux pump genes drrA, drrB, efpA, Rv2459, Rv1634, and Rv1250 were overexpressed under INH/RIF plus fresh pomegranate juice (FPJ) stress signifying the efflux pumps contribution to the overall levels of the resistance of MDR-TB isolates. Conclusion: These results displayed that the levels of drug resistance of MDR-TB clinical isolates are due to combination among drug efflux pump and the presence of mutations in target genes, a truth which is often ignored by the specialists of tuberculosis in favour of the almost undoubted significance of drug target- gene mutations for the resistance in M. tuberculosis.
Keywords: Mycobacterium tuberculosis